From pixels to parcels: Flexible, practical small-area uncertainty estimation for spatial averages obtained from aboveground biomass maps - Lucas K. Johnson; Grant M. Domke; Stephen V. Stehman; Michael J. Mahoney; Colin M. Beier (Remote Sensing of Environment, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

New allometric models for the USA create a shift in forest carbon estimation, modeling, and mapping - Lucas K. Johnson; Michael J. Mahoney; Grant M. Domke; Colin M. Beier (Forest Ecology and Management, 2025)

Declining trends in canopy disturbance across reserve forest landscapes of the northeastern US - Madeleine L. Desrochers; Elizabeth A. Clippard; Lucas K. Johnson; Colin M. Beier (Forest Ecology and Management, 2025)

Environmental Change Drivers Reduce Sapling Layer Diversity in Sugar Maple-Beech Forests of Eastern North America - Michael R. Zarfos; Gregory B. Lawrence; Colin M. Beier; Blair D. Page; Todd C. McDonnell; Timothy J. Sullivan; Mariann T. Garrison-Johnston; Martin Dovciak (Ecosystems, 2024)

Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

Estimating merchantable and non-merchantable wood volume in slash walls using terrestrial and airborne LiDAR - Nicholas Cranmer; Tao Han; Brett Chedzoy; Peter J. Smallidge; Colin Beier; Lucas Johnson; Xiangtao Xu (Forest Ecology and Management, 2024)

Mapping historical forest biomass for stock-change assessments at parcel to landscape scales - Lucas K. Johnson; Michael J. Mahoney; Madeleine L. Desrochers; Colin M. Beier (Forest Ecology and Management, 2023)

Classification and mapping of low-statured shrubland cover types in post-agricultural landscapes of the US Northeast - Michael J Mahoney; Lucas K Johnson; Abigail Z Guinan; Colin M Beier (International Journal of Remote Sensing, 2022)

Ground-Truthing Forest Change Detection Algorithms in Working Forests of the US Northeast - Madeleine L Desrochers; Wayne Tripp; Stephen Logan; Eddie Bevilacqua; Lucas Johnson; Colin M Beier (Journal of Forestry, 2022)
The need for reliable landscape-scale monitoring of forest disturbance has grown with increased policy and regulatory attention to promoting the climate benefits of forests. Change detection algorithms based on satellite imagery can address this need but are largely untested for the forest types and disturbance regimes of the US Northeast, including management practices common in northern hardwoods and mixed hardwood-conifer forests. This study ground-truthed the “off-the-shelf” outputs of three satellite-based change detection algorithms using detailed harvest records and maps covering 43,000 ha of working forests in northeastern New York.

Drought timing and local climate determine the sensitivity of eastern temperate forests to drought - Loïc D'Orangeville; Justin Maxwell; Daniel Kneeshaw; Neil Pederson; Louis Duchesne; Travis Logan; Daniel Houle; Dominique Arseneault; Colin M. Beier; Daniel A. Bishop; Daniel Druckenbrod; Shawn Fraver; et al. (Global Change Biology, 2018)
Projected changes in temperature and drought regime are likely to reduce carbon (C) storage in forests, thereby amplifying rates of climate change. While such reductions are often presumed to be greatest in semi‐arid forests that experience widespread tree mortality, the consequences of drought may also be important in temperate mesic forests of Eastern North America ( ENA ) if tree growth is significantly curtailed by drought. Investigations of the environmental conditions that determine drought sensitivity are critically needed to accurately predict ecosystem feedbacks to climate change. We matched site factors with the growth responses to drought of 10,753 trees across mesic forests of ENA , representing 24 species and 346 stands, to determine the broad‐scale drivers of drought sensitivity for the dominant trees in ENA . Here we show that two factors—the timing of drought, and the atmospheric demand for water (i.e., local potential evapotranspiration; PET )—are stronger drivers of drought sensitivity than soil and stand characteristics. Drought‐induced reductions in tree growth were greatest when the droughts occurred during early‐season peaks in radial growth, especially for trees growing in the warmest, driest regions (i.e., highest PET ). Further, mean species trait values (rooting depth and ψ 50 ) were poor predictors of drought sensitivity, as intraspecific variation in sensitivity was equal to or greater than interspecific variation in 17 of 24 species. From a general circulation model ensemble, we find that future increases in early‐season PET may exacerbate these effects, and potentially offset gains in C uptake and storage in ENA owing to other global change factors.

Estimating greenhouse gas emissions at the soil–atmosphere interface in forested watersheds of the US Northeast - Joshua Gomez; Philippe Vidon; Jordan Gross; Colin Beier; Jesse Caputo; Myron Mitchell (Environmental Monitoring and Assessment, 2016)

Effects of Harvesting Forest Biomass on Water and Climate Regulation Services: A Synthesis of Long-Term Ecosystem Experiments in Eastern North America - Jesse Caputo; Colin M. Beier; Peter M. Groffman; Douglas A. Burns; Frederick D. Beall; Paul W. Hazlett; Thad E. Yorks (Ecosystems, 2016)

Fine mapping and identification of a candidate gene for the barley Un8 true loose smut resistance gene - Wen Zang; Peter E. Eckstein; Mark Colin; Doug Voth; Axel Himmelbach; Sebastian Beier; Nils Stein; Graham J. Scoles; Aaron D. Beattie (Theoretical and Applied Genetics, 2015)

Climate change implications in the northern coastal temperate rainforest of North America - Colin S. Shanley; Sanjay Pyare; Michael I. Goldstein; Paul B. Alaback; David M. Albert; Colin M. Beier; Todd J. Brinkman; Rick T. Edwards; Eran Hood; Andy MacKinnon; Megan V. McPhee; Trista M. Patterson; et al. (Climatic Change, 2015)

Estimation of above-ground forest biomass using metrics based on Gaussian decomposition of waveform lidar data - Wei Zhuang; Giorgos Mountrakis; John J. Wiley; Colin M. Beier (International Journal of Remote Sensing, 2015)

Local climatic drivers of changes in phenology at a boreal-temperate ecotone in eastern North America - Colin M. Beier; John C. Stella; Martin Dovčiak; Stacy A. McNulty (Climatic Change, 2012)

Influence of Political Opposition and Compromise on Conservation Outcomes in the Tongass National Forest, Alaska - COLIN M. BEIER (Conservation Biology, 2008)
To understand how a highly contentious policy process influenced a major conservation effort, I examined the origins, compromises, and outcomes of the Alaska National Interest Lands Conservation Act of 1980 (ANILCA) for the Tongass National Forest. Tongass wilderness designation was among the most controversial issues in the ANILCA debate, and it faced strong opposition from influential lawmakers, land managers, and Alaska residents. To investigate the influence of this opposition on Tongass conservation outcomes, I conducted a gap analysis of Tongass reserves and a policy analysis of the ANILCA debate and traced the influence of specific interests through the amendments, negotiations, and resulting compromises needed to enact ANILCA. Overall, I found that Tongass reserves comprise a broadly representative cross‐section of ecosystems and species habitats in southeastern Alaska. Redrawn reserve boundaries, industry subsidies, and special access regulations reflected compromises to minimize the impact of wilderness conservation on mining, timber, and local stakeholder interests, respectively. Fragmentation of the Admiralty Island National Monument—the most ecologically valuable and politically controversial reserve—resulted from compromises with Alaskan Native (indigenous peoples of Alaska) corporations and timber interests. Despite language to accommodate “reasonable access” to wilderness reserves, ongoing access limitations highlight the concerns of Alaska residents that opposed ANILCA several decades ago. More broadly, the Tongass case suggests that early and ambitious conservation action may offset strong political opposition; compromises needed to establish key reserves often exacerbate development impacts in unprotected areas; and efforts to minimize social conflicts are needed to safeguard the long‐term viability of conservation measures.

Ecosystem Services and Emergent Vulnerability in Managed Ecosystems: A Geospatial Decision-Support Tool - Colin M. Beier; Trista M. Patterson; F. Stuart Chapin (Ecosystems, 2008)

Carbon limitation leads to suppression of first year oak seedlings beneath evergreen understory shrubs in Southern Appalachian hardwood forests - Colin M. Beier; Jonathan L. Horton; John F. Walker; Barton D. Clinton; Erik T. Nilsen (Plant Ecology, 2005)